A Comparison of Curriculum Structure TCSL Teacher Education Programs in Malaysia - binti Khalidar, Afiqah Sabariah (International Journal of Academic Research in Progressive Education and Development, 2019)
Teacher’s education is significant in producing a competent teacher to teach effectively. Thus the design of the curriculum structure is important to prepare prospective teachers to be equipped with the relevant subject matter knowledge and pedagogical skills. This article aims to provide a review and comparison analyses of two teaching Chinese as a second language (TCSL) pre-service teacher education programs. The study identifies the differences and similarities between two TCSL programs namely the Bachelor Degree in Education (Chinese Language Education for Primary School-PISMP-SK) conducted in IPGM (Institute of Teacher Education Malaysia) and Bachelor Degree in Teaching Chinese as a Second Language (TCSLB) which is conducted in Beijing Foreign Studies University, China (BFSU). Documentary study is adopted to identify the similarities and differences in the curriculum structure of PISMP-SK and TCSLB Chinese language programs. Analysis show that both programs consist of core course which are subject related. Both have courses for professional practice and elective core courses. However, the credit hours allocated for core courses component are different for each program, that is 36% (PISMP-SK) and 84% (TCSLB) compared to the total credit hours for each program. Meanwhile, for professional practice courses, PISMP-SK has allocated 12% of the total credit hours, but there is only 1% for TCSLB. There is a vast difference between these two programs which is there are aspect of compulsory courses in the PISMP-SK program, but not found in TCSLB program. The compulsory courses are the study of Malaysian education philosophy and beliefs, professionalism, knowledge and skills. The study shows that the PISMP-SK curriculum structure has a strong component of pedagogy in teaching Chinese language, Malaysia education philosophy and beliefs and teachers’ practice but lack in culture knowledge courses. Meanwhile TCSLB is strong that it strengthens Chinese language proficiencies and culture knowledge but lack in teaching pedagogy and professionalism knowledge. A deeper study to understand the teacher education program in preparing Chinese language teachers is needed to fill up the gap between the 2 programs for a sustainable and effective teacher education.